Inequality in exposure to crime, social disorganization and collective efficacy: evidence from Greater Manchester, United Kingdom - Lymperopoulou, Kitty (The British journal of criminology, 2022)
This paper assesses the relevance of social disorganization and collective efficacy in accounting for neighbourhood inequalities in the exposure to crime. Specifically, it questions the potential of community and voluntary organizations to enhance informal social control and reduce exposure to crime. It utilizes calls-for-service (incident) data for Greater Manchester (UK) and a Bayesian spatio-temporal modelling approach. Contrary to expectations, the research finds that measures of social disorganization (concentrated disadvantage aside) and collective efficacy hold a limited effect on neighbourhood exposure to crime. We discuss the implications of these findings for criminological inquiry and theoretical development, highlighting the necessity of such endeavour to account for the national political-economy and welfare regime of research settings